Ang paglinang ng Eucheuma. (Eucheuma farming). - Trono Jr., Gavino C.; Ganzon-Fortes, Edna T. (Quezon City, Philippines Seaweeds Information Center, UPMSI, 1989)
Pag-uma sa guso = eucheuma farming translated in Cebuano by Ms. Teresita Buchan-Antalan
Keywords: Eucheuma